Gravity and inertial load adaptive control of wall-climbing robot - Shuang Dong (The Journal of Engineering, 2018)
The five-degree-of-freedom double-legged wall-climbing robot is the most straightforward structure with the promising application because the minimum degree-of-freedom of the foot-type climbing robot with continuous movement and obstacle-overcoming capability on the vertical wall is five. Based on the prototype of the wall-climbing robot, the parameter table of the Denavit-Hartenberg (DH) model is given out, and then the positive and inverse solutions of kinematics analysis of wall-climbing robot are derived. Secondly, the system dynamics model is established based on the Lagrange equation, and the weights of inertial load acceleration torque, Coriolis force torque, centrifugal force torque and gravity torque in the dynamic equation are analysed. The design ideas of compensation gravity load and inertial load adaptive proportional differential controller is proposed according to the analysis results, and the gravity torque compensation function and general nonlinear mass function are given correspondingly to provide theoretical support to adaptive controller design. Finally, the effectiveness of the control strategy was verified by the actual control of the knee joint and ankle joint.